ARE DIGITAL SPILLOVERS IMPORTANT FOR INNOVATION AND FIRM PRODUCTIVITY? EVIDENCE FROM MALAYSIAN MANUFACTURING SECTOR - Liew Feng Mei; Choong Chee Keong; Lau Lin Sea, (Malaysian Journal of Business and Economics (MJBE), 2024)
Industry 4.0 has prompted Malaysia’s manufacturing firms to enhance their innovation and technological capabilities. Digital spillovers are vital in capturing the full impact of digitalization because the externalities created by digital adoption can be spread across the entire economy. However, scarce studies have considered digital spillovers in the analysis. This research uses the sequential CDM model to examine the relationships between firm characteristics, digital spillovers, innovation and productivity of Malaysian manufacturing firms. The firm-level data that comprises 14,723 Malaysian manufacturing firms is used for data analysis. The results reveal that the firm characteristics and horizontal digital spillover positively influence innovation and firm productivity, as opposed to the backward digital spillover. On the other hand, the effects of internal and forward digital spillovers on the innovation output and firm productivity are relatively mixed. It suggests that manufacturing firms respond differently to information flows from various stakeholders on digital platforms, applying them uniquely to their production methods and business operations. The government is encouraged to support manufacturing firms, especially the SMEs, in leveraging digitalization to improve their performance and competitiveness.